Perbandingan Prestasi Belajar Siswa pada Mata Pelajaran Matematika Menggunakan Model Pembelajaran Kooperatif Tipe Make a Match, Snowball Throwing, dan Think Pair Share (TPS) Pada Pokok Bahasan Bilangan Bulat dan Pecahan Siswa Kelas VII SMPN 1 Bringin - Erny Untari; Indra Puji Astuti; Doni Susanto (Universitas Veteran Bangun Nusantara, 2022)
This study aims to determine whether there are differences in mathematics learning achievement in students who are taught using cooperative learning methods of Make a Match, Snowball Throwing, and Think Pair Share types. This study uses an experimental method with a population of all seventh-grade students of SMP Negeri 1 Bringin in Odd Semesters for the 2019/2020 Academic Year. The sample used for the experimental class is 3 classes with 90 students. Sampling technique by means using a simple random sample (Simple Random Sampling). While the data collection method uses the test method. Hypothesis testing in this study was carried out using the prerequisite analysis test, namely the normality test using Chi Square and homogeneity using Bartlett. Furthermore, the analysis technique uses the Non-Parametric test (Kruskal Wallis). The result of this research is that there is no significant difference between the three learning methods of Make a Match, Snowball Throwing and Think Pair Share on students' mathematics learning achievement.